Rancangan Geometri Peledakan Untuk Mencapai Target Fragmentasi Ideal Berdasarkan Nilai Blastibility Index Pada Tamka PT. Allied Indo Coal Jaya Kota Sawahlunto - Syarif Hidayattullah; Bambang Heriyadi (Departemen Teknik Pertambangan FT UNP, 2019)
Abstract. In blasting, the fragmentation of blasting results is influenced by the characteristics of rock masses, geological structures, groundwater, and others. Blastibility Index is a measurement of geological conditions and rock mass characteristics in blasting, in the measurement of blastibility index There are several parameters such as the rock mass description obtained RQD by 71,96% classified as a blocky rock, The joint mass description is classified as intermediate (space 0,1 m – 1 m), joint plane orientation (JPO) dip into face, specific grafity influence (25 x 2,68 - 50) obtained 17, hardness of 5,5. The blastibility index gained 51,25 with the 6,15 rock factor. In the lily chart is acquired geometry blasting design with a burden of 2,03m , spacing 2,85m, the dept of blast holes 6,09 m, PC 4,37 m, stemming 1,6 m, subdrilling 0,608 m, the explosives weight 17,994 kg/hole, powder factor 0,567 kg/m3. Actual fragmentation of the geometry design with the first lily chart is embraced by the software Splitdesktop 2.0 obtained a fragmentation size of 50 cm at 6,31%. Design of the second blasting geometry burden 2,337 m, space 3,272m, the depth of the blast hole 7,011 m, PC 5,375 m, stemming 1,635 m, explosive weight 20,715kg/hole, powder factor 0,43 kg/m3.